CHROMOSPHERIC ACTIVITY OF THE FLARE STAR YZ CMI IN QUIESCENCE ACCORDING TO THE FAST SPECTRAL MONITORING DATA - Verlyuk, I. A. (Одеські астрономічні публікації, 2016)
Spectral monitoring of the flare star YZ CMi (U = 12.9, B = 12.7, V = 11.1) was carried out on the Zeiss-600 telescope at the Peak Terskol Observatory. We used a low resolution grating spectrograph with spectral resolution of 100 Å and time resolution from 2 to 30 s. The spectra of the star in the quiescent state show variability in the lines Hβ, Hγ, Mg b, possibly in CaII K + Hε. Variations of the equivalent widths of the order of several percents were detected. The characteristic time of variations is about of a few minutes. The observed variations indicate the non-stationary activity of the flare star YZ CMi chromosphere in the quiescent state. Stars; variability; methods: statistical; stars: late-type